Differential Subordination And Coefficients Problems Of Certain Analytic Functions - Shamani, Supramaniam (2014)

(untitled)
Let A be the class of normalized analytic functions f on the unit disk D, in the form f(z) = z+ P1n =2 anzn: A function f in A is univalent if it is a one-to-one mapping. This thesis discussed ¯ve research problems. Lambangkan A sebagai kelas fungsi analisis ternormal pada cakera unit D berbentuk f(z) = z + P1n =2 anzn: Fungsi f dalam A adalah univalen jika fungsi tersebut ialah pemetaan satu ke satu. Tesis ini mengkaji lima masalah penye- lidikan.